Metal induced inhomogeneous Schottky barrier height in AlGaN/GaN Schottky diode - Shin, Jong-Hoon; Park, Jinhong; Jang, SeungYup; Jang, T.; Sang Kim, Kyu (Applied physics letters, 2013)
The dependence of barrier height inhomogeneity on the gate metal has been investigated for the AlGaN/GaN Schottky diode. The analysis from the electroreflectance spectroscopy measurement for different types of Schottky gate metals tried (in this case, Au, Pt, Pd, and Ni) reveals that the surface donor states of AlGaN/GaN heterostructure strongly depends on the type of Schottky gate metals used, which suggests that barrier height inhomogeneity is strongly dependent on the gate metal. The X-ray photoelectron spectroscopy also reveals a strong correlation between the barrier height inhomogeneity and the gate metal type.